Pengaruh Proses Pembuatan Terhadap Karakteristik Minyak Kelapa - Lestari, Endang Putri; Gugule, Sanusi; Fatimah, Feti; Maanari, Chaleb (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2025)
Coconut oil is one of the vegetable oils widely used in the food, cosmetic, and pharmaceutical industries due to its high content of saturated fatty acids, particularly lauric acid. This study was conducted on the effect of coconut oil processing methods on the characteristics of the resulting coconut oil. Three processing methods were applied: non-heating, fermentation, and direct heating. A transesterification step was carried out to determine the fatty acid profile and its derivatives. The characterization of coconut oil compounds included measurements of density, acid value, peroxide value, and ester value, as well as analysis of fatty acid compounds using Gas Chromatography-Mass Spectrometry (GC-MS). The results showed that the best method for producing coconut oil was the non-heating process, with the following physicochemical properties: yield of 13.5%, acid value of 0.20 mg KOH/g, peroxide value of 2.00 meq/kg, and ester value of 223.28 mg KOH/g. The main components identified from the transesterified coconut oil were dodecanoic acid methyl ester (methyl laurate), methyl tetradecanoate, and hexadecanoic acid methyl ester.